MFN2 deletion of exons 7 and 8: founder mutation in the UK population. Issue 2 (June 2015) - Carr, Aisling S.; Polke, James M.; Wilson, Jacob; Pelayo‐Negro, Ana L.; Laura, Matilde; Nanji, Tina; Holt, James; Vaughan, Jennifer; Rankin, Julia; Sweeney, Mary G.; Blake, Julian; Houlden, Henry; et al.
Abstract Mitofusin 2 (MFN2) mutations are the most common cause of axonal Charcot‐Marie‐Tooth disease (CMT2). The majority are inherited in an autosomal dominant manner but recessive and semi‐dominant kindreds have also been described. We previously reported a deletion of exons 7 and 8 resulting in nonsense‐mediated decay, segregating with disease when present in trans with another pathogenic MFN2 mutation. Detailed clinical and electrophysiological data on a series of five affected patients from four kindreds and, when available, their parents and relatives were collected. MFN2 Sanger sequencing, multiplex ligation probe amplification, and haplotype analysis were performed. A severe early‐onset CMT phenotype was seen in all cases: progressive distal weakness, wasting, and sensory loss from infancy or early childhood. Optic atrophy (four of five) and wheelchair dependency in childhood were common (four of five). All were compound heterozygous for a deletion of exons 7 and 8 in MFN2 with another previously reported pathogenic mutation (Phe216Ser, Thr362Met, and Arg707Trp). Carrier parents and relatives were unaffected (age range: 24–82 years). Haplotype analysis confirmed that the deletion had a common founder in all families.